Application of multiserver queueing to call centres - Majakwara, Jacob (Rhodes University, Faculty of Science, Department of Statistics, 2010)
The simplest and most widely used queueing model in call centres is the M/M/k system, sometimes referred to as Erlang-C. For many applications the model is an over-simplification. Erlang-C model ignores among other things busy signals, customer impatience and services that span multiple visits. Although the Erlang-C formula is easily implemented, it is not easy to obtain insight from its answers (for example, to find an approximate answer to questions such as "how many additional agents do I need if the arrival rate doubles?"). An approximation of the Erlang-C formula that gives structural insight into this type of question would be of use to better understand economies of scale in call centre operations. Erlang-C based predictions can also turn out highly inaccurate because of violations of underlying assumptions and these violations are not straightforward to model. For example, non-exponential service times lead one to the M/G/k queue which, in stark contrast to the M/M/k system, is difficult to analyse. This thesis deals mainly with the general M/GI/k model with abandonment. The arrival process conforms to a Poisson process, service durations are independent and identically distributed with a general distribution, there are k servers, and independent and identically distributed customer abandoning times with a general distribution. This thesis will endeavour to analyse call centres using M/GI/k model with abandonment and the data to be used will be simulated using EZSIM-software. The paper by Brown et al. [3] entitled "Statistical Analysis of a Telephone Call Centre: A Queueing-Science Perspective," will be the basis upon which this thesis is built.
Keywords: Call centers; ERLANG (Computer program language); Queuing theory